USE OF INFORMATION COMPETENCIES IN PRACTISE - KOŇUŠÍKOVÁ, Marianna; PAVÚROVÁ, Edita (Trends in education, 2009)
The development of information competencies currently devotes to education in primary school, then the competencies are developed on secondary and tertiary levels. The development of information competencies specify multiple skills that graduate schools should be developed and operated. Their current development of education responds to the most frequently requested skills graduates. The contribution describes the use of information and communication technologies (ICT) in education and the importance of skills and competencies development for practice. The contribution shows their necessity in today's modern "over-technicized" world. ICT and their use are significant in the exercise of graduates in their profession. They ensure flexibility and continuity of a connection between the education and the exercise in profession.
Keywords: network; information and communication technologies; key competencies; information competencies; application in the job.